2018
DOI: 10.5114/aoms.2018.73975
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of miR-203a by lncRNA PVT1 in multiple myeloma promotes cell proliferation

Abstract: IntroductionEmerging evidence has indicated that long non-coding RNAs (lncRNAs) play vital roles in multiple myeloma (MM) development and progression. However, the underlying mechanism of PVT1 in MM remains unclear.Material and methodsQRT-PCR was used to detect the expression of PVT1 and miR-203a in MM samples and cell lines. The effects of PVT1 on MM cell proliferation and apoptosis were determined by CCK8 assay and flow cytometer assay, respectively. Bioinformatics methods were used to identify the downstrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 19 publications
0
39
0
Order By: Relevance
“…ose data indicated that suppression of KIF22 inhibited cell proliferation in vitro. Although the results are different, we also could use similar methods to explore the mechanism [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…ose data indicated that suppression of KIF22 inhibited cell proliferation in vitro. Although the results are different, we also could use similar methods to explore the mechanism [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from MIAT, many lncRNAs were reported to play an active role in many pathogeneses of human diseases. For example, lncRNA PVT1 was once reported to represent a potential therapeutic target for the treatment of multiple myeloma because it could promote multiple myeloma cell proliferation and induce cell apoptosis by inhibiting its target gene, miR-203a [48]. And lncRNA, UBE2CP3-001, was found to be potentially applied in the anti-glioma therapy [49].…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, this evidence could depict a novel molecular paradigm underlying the pathogenesis of 8q24 rearrangement-positive MM. PVT1 knockdown in MM cell lines inhibited cell proliferation and promoted apoptosis [48] through restoration of expression of miR-203a [68] (Fig. 3).…”
Section: Multiple Myelomamentioning
confidence: 93%
“…Elevated PVT1 levels were detected in MM BM cells compared with normal tissue [68] and primarily in MYCrearranged MM cases [69]. In particular, high PVT1 was associated with MM carrying recurrent MYC fusion genes (with IGH, IGK, IGL, TXNDC5/BMP6, FOXO3 and FAM46C partner genes) or complex rearrangements involving more than five loci, or hyperdiploid cases, that also overexpressed MYC [69].…”
Section: Multiple Myelomamentioning
confidence: 96%
See 1 more Smart Citation